Mechanical Thrombectomy in Perioperative Strokes: A Case–Control Study. Issue 11 (November 2017) - Premat, Kévin; Clovet, Olivier; Frasca Polara, Giulia; Shotar, Eimad; Bartolini, Bruno; Yger, Marion; Di Maria, Federico; Baronnet, Flore; Pistocchi, Silvia; Le Bouc, Raphaël; Pires, Christine; Sourour, Nader; et al.
Abstract : Background and Purpose—: Perioperative strokes (POS) are rare but serious complications for which mechanical thrombectomy could be beneficial. We aimed to compare the technical results and patients outcomes in a population of POS versus non-POS (nPOS) treated by mechanical thrombectomy. Methods—: From 2010 to 2017, 25 patients with POS (ie, acute ischemic stroke occurring during or within 30 days after a procedure) who underwent mechanical thrombectomy (POS group) were enrolled and paired with 50 consecutive patients with nPOS (control group), based on the occlusion's site, National Institute of Health Stroke Scale, and age. Results—: Respectively, mean age was 68.3±16.6 versus 67.2±16.6 years ( P =0.70), and median National Institute of Health Stroke Scale score at admission was 20 (interquartile range, 15–25) versus 19 (interquartile range, 17–25; P =0.79). Good clinical outcome (modified Rankin Scale score of 0–2 at 3 months) was achieved by 33.3% (POS) versus 56.5% (nPOS) of patients ( P =0.055). Successful reperfusion (modified Thrombolysis In Cerebral Infarction score of ≥2b) was obtained in 76% (POS) versus 86% (nPOS) of cases ( P =0.22). Mortality at 3 months was 33.3% in the POS group versus 4.2% (nPOS) ( P =0.002). The rate of major procedural complications was 4% (POS) versus 6% (nPOS); none were lethal. Average time from symptoms' onset to reperfusion was 4.9 hours (±2.0) in POS versus 5.2 hours (±2.6). Conclusions—: Successful reperfusion seems accessible in POS within a reasonable amount of time and with a good level of safety. However, favorable outcome was achieved with a lower rate than in nPOS, owing to a higher mortality rate. Abstract : Supplemental Digital Content is available in the text.